THE EFFECT OF DIGITALIZATION OF COMPANY SYSTEMS ON EMPLOYEE PERFORMANCE WITH TALENT MANAGEMENT AS A MODERATING VARIABLE - Dita Dismalasari Dewi; HM. Saiful Bahri; Muhamad Azkia; Adi Suroso; Agung Widarman (Adisam Publisher, 2024)
This research is quantitative research with an exploratory approach, namely an approach that uses a number of previous studies as a fundamental foundation to strengthen the argumentation construction in this. The data used in this research is primary data obtained from Maspion employees throughout Indonesia. The data in the research were analyzed using the smart PLS 4.0 analysis tool. The result in this article show that the researcher's assumptions used as hypotheses are acceptable because the P-Values are below 0.05, namely 0.005 and lead to positive. This is due to the simplicity of the system, ease of completing work, and other things that employees feel as a result of the digitalization of the company's system. This is in line with previous research. Apart from that, the second hypothesis in this research can also be proven because the P-Vlaues value is positive and is below the 0.05 significance level, namely 0.000. This means that good talent management can produce and maintain good quality human resources, can use technology well, can take advantage of good digitalization of the Company's systems, and will have a good impact on employee performance. Thus the first and second hypotheses in this article can be proven.